ANALYSIS OF THE INFLUENCE OF MANAGEMENT ACCOUNTING INFORMATION SYSTEM (MAIS) AND COMPETITIVE ADVANTAGE ON SMEs PERFORMANCE IN MALANG CITY - Syafaat, Farid Azhar; Ananda Rizky, Tri; Novianti, Ramadhinta; Ratnasari, Tri; Wuryaningsih, Wuryaningsih (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Market competition has generated upheaval, pressure, risk, and uncertainty for businesses. Organizations must quickly adapt to their market environment to gain and maintain competitive advantage. The relevance of Management Accounting Information System (MAIS) plays a crucial role in enhancing this advantage by providing managers with timely and relevant internal information and supporting decision-making that aligns with strategic objectives related to quality, cost efficiency, and market responsiveness. This study examines the influence of MAIS and competitive advantage on the performance of small and medium-sized enterprises (SMEs) in Malang City. A quantitative correlational survey design was employed, gathering data from 129 respondents via a Google Form survey targeting SMEs in Malang City. The findings indicate that competitive advantage significantly and positively influences SMEs performance, supporting the hypothesis that stronger competitive advantage leads to better business performance. However, MAIS does not show a significant direct effect on competitive advantage, suggesting its role may be more indirect, contributing to informed and efficient decision-making that supports other business aspects. The study underscores the importance of focusing on strategies such as product innovation, service quality improvement, and operational efficiency to enhance competitive advantage and, consequently, SMEs performance. While MAIS did not show a significant direct impact on competitive advantage, its use remains important for supporting comprehensive business strategies. Future research should explore additional variables and consider mediating and moderating factors to provide a deeper understanding of the dynamics between MAIS, competitive advantage, and SMEs performance.